Kompetensi Guru Menerapkan Pembelajaran Bermakna Menuju Merdeka Belajar dalam Membangun Karakter Anak - Warni Tune Sumar (Jambura Early Childhood Education Journal, 2021)
Competent teachers are able to create a happy learning atmosphere, both for students and teachers. Therefore teachers who have professional competence must teach by creating independent learning so that the learning process can make students more creative, innovative and can create a happy atmosphere. Meaningful learning is learning that emphasizes the use of knowledge meaningfully and the learning process is more directed at learning activities on students' thinking abilities. Learning that liberates the process of formulating meaning actively involves integrated skills using problems in real contexts. A meaningful learning process will condition the birth of intelligent children as well as character. It is said meaningful learning if the school is able to accommodate all the potential of its students, and the teacher is able to understand and guide learning in accordance with the talents of student interests. Whereas for students, it is always embedded that school is fun. In free learning, the teacher besides acting as a source of learning, also acts as a learning facilitator. As a learning facilitator, of course the teacher must design a learning that is fun so that students can achieve the expected learning goals. Teachers who have professional competence can realize concepts and reflect freedom of learning. Teachers are required to be more creative and innovative in developing learning materials.